Job Search and the Age-Inequality Profile - Petra Marotzke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Empirical studies find that the age-variance profile of wages is U-shaped. The objective of this paper is to explore the driving forces of the U-shape in a model with search frictions. I introduce endogenous search effort and a fixed retirement age into Cahuc, Postel-Vinay, and Robin s (2006) strategic wage bargaining model with counteroffers and heterogeneous firm-worker matches. Three factors shape the age-inequality profile of wages in the model economy: the time horizon before retirement, match heterogeneity, and the worker's bargaining power. Because the working life is finite, the optimal search effort decreases with age. Furthermore, the probability of meeting an outside firm with a higher match quality decreases in the quality of the current match. The bargaining power parameter influences the worker's reservation wage. The model can reproduce the U-shape of the age-inequality profile of wages if the bargaining power of workers is sufficiently high. Furthermore, the model captures the shapes of the empirically observed age profiles of average wages, the unemployment rate, the unemployment to employment transition rate, and the employment to employment transition rate.
Keywords: J31; J41; J64; 330